Fostering Reading Habits in Secondary Students through English Literature Supplementary Texts - Hendarto, Vyrna; Mulyadi, Dodi (Universitas Muhammadiyah Semarang, 2024)
This applied research examines the impact of using English literature supplementary texts to nurture reading habits in Year 8 students. The intervention aimed to increase students' independent reading hours by incorporating engaging literature into the English curriculum. The quantitative data were collected through pre- and post-intervention surveys, revealing a significant 56% increase in independent reading hours after the intervention. This growth indicates that supplementary texts can effectively enhance students' interest in reading outside the classroom. The qualitative data from student interviews and focus groups supported these findings. Students reported greater enjoyment and interest in reading, attributing it to the engaging nature of the supplementary texts. Many also noted improvements in their comprehension and analytical skills. In conclusion, incorporating English literature supplementary texts has successfully nurtured reading habits among Year 8 students. The significant increase in independent reading hours and positive feedback highlight the potential of this approach to foster a lifelong love for reading and improve literacy skills. Future recommendations include continued use of diverse supplementary texts and regular assessments to monitor long-term impacts.